Understanding maladaptive responses to rejection: Aggression with an audience. Issue 1 (2nd January 2017) - DeBono, Amber; Layton, Rebekah L.; Freeman, Nicholas; Muraven, Mark
ABSTRACT: Logically, responding aggressively to rejection is maladaptive because one is unlikely to seek a relationship with an aggressor. We predict that when concealed, the illogical aggressive response to rejection is more likely, whereas when the rejected individuals' aggressive responses are perceived as public, the aggressive acts may be reduced. Participants were rejected by others (Experiment 1) or were either accepted or rejected during an online ball-tossing game (Experiment 2) and were then given an opportunity to aggress publicly or privately. Across experiments, when the opportunity to aggress was made public, rejected participants exhibited less aggressive behavior. When concerned about the perception of their public aggressive responses by others, rejected individuals' aggressive responses diminished compared with those whose actions were private. Crucially, this extended to aggression visible only to neutral others, suggesting that effects cannot solely be due to fear of retribution.